Pengaruh Standar Akuntansi Keuangan Daerah, Teknologi Informasi dan Kualitas Aparatur Terhadap Kualitas Laporan Keuangan - Yanto; Qotrun Nada, Shalha (Fakultas Ekonomi dan Bisnis Universitas Islam Nahdlatul Ulama Jepara, 2024)
The aim of the research is to analyze the influence of the application of regional financial accounting standards, the use of information technology and the quality of regional government apparatus on the quality of regional financial reports in the Regional Apparatus Organization (OPD) of Jepara Regency. The population is 46 OPD financial managers. The research results show that the application of regional financial accounting standards has a significant positive effect on the quality of regional financial reports, as shown by the value of tcount (2.006) > ttable (1.65630) and sig. 0.016 < 0.05; The use of information technology has a significant positive effect on the quality of regional financial reports, as shown by the value of tcount (2.567) > ttable (1.65630) and sig. 0.009 < 0.05; and the quality of regional government apparatus has a significant positive effect on the quality of regional financial reports as shown by the value of tcount (2.434) > ttable (1.65630) and sig. 0.015 < 0.05.